The characteristics of early pandemic advertising - Kowalewska, Kinga (Scripta Neophilologica Posnaniensia, 2021)
The aim of this paper is to examine early pandemic commercials and show the main changes in their focus from the point of view of communication. In terms of the contents, COVID-19 lockdown, heroism of health care workers, social distancing, online learning, remote work, and the strong shift towards online communication are underlined with an enormous stress put on such values as family, helping each other and being together in these difficult times. Characteristic nonverbal components of commercials referring to the pandemic situation include, for example, sentimental piano music, dimmed colours, a specific style of filming, or showing ordinary people as actors. Finally, it is noticed that some ad makers decide to use the sense of humour in their spots. In conclusion, the coronavirus pandemic and its effects can be easily observed on every level of an advertising message.